Sangatta Delta Evolution with an Updated Miocene Paleogeography - Purnama A. Suandhi; A. Bachtiar; Prihatin T. Setyobudi; Endi Nurjadi; Andi Mardianza; B. Dody Harisasmita; M. Arifai; Dwi Hendro H. N (Berita Sedimentologi, 2017)
The Sangatta Delta is one of significant deltas which developed during Miocene in the northern part of Kutai Basin. Significant hydrocarbons and coals have been produced from Middle – Lower Miocene fluvio-deltaic sediments along the onshore – offshore parts of the Lower Kutai Basin since 1970 until present. The Sangatta Delta’s architecture was already published since 1994 based on subsurface data around the Sangatta Field. However, information on stratigraphy and sedimentological model only covered the Middle – Lower Miocene sections and there were no publication of its complete stratigraphy succession for more than 15 years.Recently, many road accesses have been developed, connecting villages and districts around Kutai Timur Regency. Most of the roads cut across perpendicularly to stratigraphy strikes measured from surface outcrops, including Miocene Section. Integrated surface geological study by using continuous measurement sections along the road accesses was used in generating composite, Miocene stratigraphic columns, which display information of stratigraphy, facies succession and paleogeography of Miocene deposits. Evolution of Sangatta Delta was interpreted by using chronostratigraphy built from outcrops observation.The Sangatta Delta development was controlled by Rantau Pulung – Mangkupa paleohigh (Rantau Pulung Island), which is bound by NE-SW and N-S strike slip faults system called Bengalon – Batuampar Slip Faults (NE-SW) and Rantau Pulung – Himba Lestari Slip Faults (N-S). Those faults represent old basement faults that were reactivated several times during Neogene time and they controlled the accommodation space and structural development around the Sangatta Delta.The delta development started in Early Miocene when at least two fluvial deltaic parasequence sets prograded toward east. During that time, the Rantau Pulung island was an exposed area, surrounded by marine environment. The delta continued to develop and became larger during Middle – Late Miocene as regional inversion and uplift took place at Kuching High to the west of the delta. More than ten stacking fluvial deltaic parasequence sets have been identified from stratigraphic composite columns and they all show progradation toward east. The stratigraphy deposited by the Early – Late Miocene progradation cycles could become new exploration targets around the Sangatta area, especially deep Neogene target or deepwater plays related to deltaic environment in distal facies area.